La percepción de los mexicanos sobre la sociedad civil: un estudio acerca de la violencia entre los años 2006-2016 - Caetano, Gabriel Fernandes (2018)
The aim of this thesis is to investigate the perception of Mexican students from Mexico City about the actions taken by the Civil Society and its actors in the face of violence during the ten years of the war on drug trafficking, between 2006 and 2016. Methodologically, the work has a qualitative approach using a semi-structured questionnaire as instrument of data collection. The collected data were analyzed using IRAMUTEQ software. Participants were 78 college students, 41% from a public university (Universidad Nacional Autónoma de México - UNAM), and 59% from a private institution (Universidad Iberoamericana - UIA), mostly women (56, 4%), and aged between between 20 and 38 years (M = 24.43, SD = 3.67). From the analysis of the Hierarchical Describing Classification, the corpus was divided into five classes that were named from their most representative descriptors: Experiences of violence; Daily violence and political corruption; The limits of the Mexican CS and its actors; Perceptions about the MPJD and # YoSoy132; General perception about the Mexican CS. The results showed that most participants (51.3%) perceive as positive the performance of the Mexican civil society and its actors in the scenario of violence resulting from the ten years of the war on drug trafficking.